S-Box Design Utilizing 3D Chaotic Maps for Cryptographic Application - Namuq, Jenan Ayad (Basrah Journal for Engineering Sciences, 2024)
In the realm of cryptography, the Substitution-box (S-box) is a critical component for enhancing the security of encryption algorithms. The inherent characteristics of Chaos, such as sensitivity to beginning conditions and unpredictability, make it a highly suitable choice for encryption applications. In this paper, proposed a method for generating S-Boxes using 3D chaotic maps algorithms including (Cat map, Henon map, Sine map, and Cosine map). The primary focus is on enhancing the security and efficiency of cryptographic systems by leveraging the inherent complexity and unpredictability of chaotic maps. The design methodology focuses on achieving high non-linearity, optimal avalanche effect, and Strict Avalanche Criterion ( SAC ), ensuring that minor changes in plaintext result in significant alterations in the ciphertext. Our study presents a detailed analysis of the generated S-Boxes, demonstrating their robustness against common cryptographic attacks. Key findings include significant improvements in nonlinearity, differential uniformity, and bijectivity compared to traditional methods. The test findings and performance analysis indicate that our proposed S-Box exhibits much lower values of Linear Probability ( LP ) and Differential Probability ( DP ), while maintaining a suitable average value of nonlinearity. Additionally, discussed the broader implications of our findings, emphasizing how the proposed method can be employed to produce high-quality analytical results that enhance the security measures of cryptographic applications. This work adds valuable context to existing research and highlights the potential for our model to outperform conventional S-Box generation techniques.